Electrospray Ionization mass spectrometry: a powerful platform for noble-metal nanocluster analysis - Chen, Tiankai; Yao, Qiaofeng; Nasaruddin, Ricca Rahman; Xie, Jianping (Wiley-VCH Verlag, 2019)
Electrospray ionization mass spectrometry (ESI-MS) is an analytical technique that measures the mass of a sample through “soft” ionization. Recent years have witnessed a rapid growth of its application in noble-metal nanocluster (NC) analysis. ESI-MS is able to provide the mass of a noble-metal NC analyte for the analysis of their composition (n, m, q values in a general formula [MnLm]q), which is crucial in understanding their properties. This review attempts to present various developed techniques for the determination of the composition of noble metal NCs by ESI-MS. Additionally, advanced applications that use ESI-MS to further understand the reaction mechanism, complexation behavior, and structure of noble metal NCs are introduced. From the comprehensive applications of ESI-MS on noble-metal NCs, more possibilities in nanochemistry can be opened up by this powerful technique.